Pengaruh Reward, Pengalaman, Motivasi, dan Kedisiplinan Kerja Terhadap Kinerja Karyawan PT. XYZ - Angelica Renataputri; Flora Valencia; Wulan Agus Styaningsih; Ignatius Ario Sumbogo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
Export and import activities are very influential to the economic development of Indonesia, especially in this pandemic situation. The growth rate had significantly dropped over the past 2 years. The situation in the recent year had changed with the rapid growth rate of export and import per March 2022. One of the many companies that are affected by the pandemic situation is PT XYZ. This company focuses on exporting and importing goods. The main purpose of this research is to acknowledge how rewards, experiences, motivation, and work discipline towards employees can have an impact on the overall performance of a company. This research utilizing 4 independent variables and 1 dependent variable using quantitative research with the method of distributing questionnaires to 103 employees with non-probability technique saturated sampling. The result shows that the variables of motivation and work discipline have a significant impact on the employee’s working performance in PT XYZ. However, the other variables such as reward and work experience do not have an impact on the employee’s working performance.